The Nexus between Supplier Selection Practices and Procurement Function Performance: A Kenyan Public Universities Perspective - Musyoka, Festus; Namusonge, Gregory; Musau , Enock (International Journal of Supply Chain Management, 2024)
Purpose: This study aimed to unveil how supplier assessment and governance influenced procurement function performance. Methodology: The study employed a post-positivist research philosophy and a causal-comparative design. The study used multi-stage sampling to arrive at the sample of respondents of 93 procurement officers. Quantitative data was collected through self-designed structured questionnaires and analyzed using Statistical Packages for Social Sciences (SPSS version 27). Demographically, the study included predominantly experienced, educated male and female professionals. Findings: The findings of the study revealed that supplier selection significantly and positively impacted procurement function performance. Specifically, supplier assessment exhibited a noteworthy positive effect on procurement function performance (Î² = .517, p < .001), underlining the critical role of due diligence, evaluations, and appraisals among suppliers. Similarly, supplier governance demonstrated a substantial positive effect on procurement function performance (Î² = .310, p = .001), highlighting the significant roles of supplier selection transparency and conflict resolution mechanisms in procurement processes. Unique Contribution to Theory, Practice and Policy: This study unveiled how supplier assessment and governance influenced procurement function performance anchored in the Resource Dependence Theory (RDT), The study's results confirmed that robust supplier selection practices, grounded in supplier assessment and governance, significantly improved procurement function performance in Kenyan public universities. Strengthening supplier assessment protocols and governance mechanisms emerged as imperative for optimizing outcomes in procurement functions.